2012
DOI: 10.1029/2011jb008717
|View full text |Cite
|
Sign up to set email alerts
|

Seismic structure near the inner core boundary in the south polar region

Abstract: [1] It is crucial to obtain good spatial coverage of seismic data points for better understanding the Earth's core, but the core beneath the polar regions remains largely unexplored. We analyzed differential traveltimes and amplitude ratios of core phases whose raypaths run beneath Antarctica for determining the V p and Q p structure near the inner core boundary in the south polar region. The model we obtained (south polar region model, SPR) is described relative to the preliminary reference Earth model (PREM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…The total thickness of the isotropic layer is also different for the two hemispheres, of the order of 100 km beneath the western hemisphere, extending deeper (400 km) beneath the Eastern one (Creager, 2000;Garcia and Souriau, 2000b). Monnereau et al (2010) find a smooth transition between the two hemispheres, a result also supported by data sampling the high southern latitudes (Ohtaki et al, 2012). By contrast, and Miller et al (2013) propose sharp boundaries, but the same data may be as well explained by smooth variations in inner core texture from one hemisphere to the other (Geballe et al, 2013).…”
Section: Depth Dependence Of the Anisotropy And Hemispherical Variationsmentioning
confidence: 52%
See 1 more Smart Citation
“…The total thickness of the isotropic layer is also different for the two hemispheres, of the order of 100 km beneath the western hemisphere, extending deeper (400 km) beneath the Eastern one (Creager, 2000;Garcia and Souriau, 2000b). Monnereau et al (2010) find a smooth transition between the two hemispheres, a result also supported by data sampling the high southern latitudes (Ohtaki et al, 2012). By contrast, and Miller et al (2013) propose sharp boundaries, but the same data may be as well explained by smooth variations in inner core texture from one hemisphere to the other (Geballe et al, 2013).…”
Section: Depth Dependence Of the Anisotropy And Hemispherical Variationsmentioning
confidence: 52%
“…PKP(BC) shows that P-velocities are identical inside and outside the tangent cylinder (Ohtaki et al, 2012;Souriau et al, 2003b;Yu et al, 2005), a result confirmed by normal mode analyses (Ishii and Dziewonski, 2005). No evidence of heterogeneity could be firmly established.…”
Section: Search For a Three-dimensional Structure Inside The Liquid Corementioning
confidence: 80%
“…However, the proposition of the Fe‐rich F layer has not been firmly supported by seismic observations yet. Several seismic models have a velocity close to or lower than that of AK135 in the layer [e.g., Souriau and Poupinet , ; Song and Helmberger , ; Zou et al , ]; other models are close to PREM [ Kaneshima et al , ; Yu et al , ; Ohtaki et al , ]. The V p profile of the F layer has been poorly resolved because of (1) the nonuniqueness of the profiles inherent in previous observations and (2) the interdependence of the V p of the F layer and the seismic structure elsewhere in the Earth, as described in detail in section 2.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that the V p values in the F layer are intermediate between those of AK135 and PREM, and that the gradient of V p with respect to depth is steeper than that of AK135. V p profiles with much smaller gradient in the F layer, like those of the AK135 and (south polar region) SPR [ Ohtaki et al , ], are not supported by our observations.…”
Section: Introductionmentioning
confidence: 99%
“…If one is suitable, it can serve as a reference for the core's constitution from which changes from an adiabatic, well-mixed state may be assessed. Wavespeeds lower than PREM observed at the top and bottom of the outer core (Helffrich and Kaneshima 2010;Ohtaki et al 2012;Zou et al 2008) are not expected from traditional views of core behavior (where lower wavespeeds are associated with higher densities and vice versa), though here I focus only the top of the core in order to prove the viability of the approach.…”
Section: Introductionmentioning
confidence: 99%